Evaluating land suitability for kemiri (Aleurites moluccana) as a multi-purpose tree species in community agroforestry land within Langkat District, North Sumatra - Rahmawaty; Sintike Frastika; Abdul Rauf; Ridwanti Batubara; Mohd Hasmadi Ismail; Seca Gandaseca (Global Forest Journal, 2024)
Evaluating land suitability for Aleurites moluccana in community agroforestry land within Langkat District, North Sumatra, is crucial for promoting sustainable development, enhancing livelihoods, and preserving ecosystems while honoring local traditions and cultures. The primary objective of this research was to evaluate and map the land suitability for A. moluccana within Langkat District, located in North Sumatra, Indonesia. To gather the necessary data, this study employed a survey method, involving the collection of soil samples from ten distinct land units within the field. The assessment of land suitability was carried out using the matching method. Geographic Information System (GIS) technology was utilized to create maps illustrating the distribution of land suitability, while a Global Positioning System (GPS) was employed to accurately record the coordinates of the collected soil samples. The findings revealed that within Gunung Ambat, Simpang Kuta Buluh, Rumah Galuh, and Telagah Village, the actual land suitability classes for A. moluccana were classified as moderately suitable (S2) and marginally suitable (S3). The prevailing limiting factors in this region were temperature (tc) and the characteristics of the root zone medium (rc). Consequently, this influenced the potential land suitability classes for A. moluccana, resulting in classifications ranging from highly suitable (S1) to moderately suitable (S2) and marginally suitable (S3). By implementing land suitability evaluation for A. moluccana in community agroforestry land, promoting sustainable land use, enhancing livelihoods, and conserving natural resources.